Effects of Pre-race Apneas on 400-m Freestyle Swimming Performance. Issue 3 (March 2020) - Robertson, Craig; Lodin-Sundström, Angelica; O'Hara, John; King, Roderick; Wainwright, Barney; Barlow, Matthew
Abstract : Abstract: Robertson, C, Lodin-Sundström, A, O'Hara, J, King, R, Wainwright, B, and Barlow, M. Effects of pre-race apneas on 400-m freestyle swimming performance. J Strength Cond Res 34(3): 828–837, 2020—This study aimed to establish whether a series of 3 apneas before a 400-m freestyle time-trial affected swimming performance when compared with and combined with a warm-up. Nine (6 males and 3 females) regional to national standard swimmers completed four 400-m freestyle time-trials in 4 randomized conditions: without warm-up or apneas (CON), warm-up only (WU), apneas only (AP), and warm-up and apneas (WUAP). Time-trial performance was significantly improved after WUAP (275.79 ± 12.88 seconds) compared with CON (278.66 ± 13.31 seconds, p = 0.035) and AP (278.64 ± 4.10 seconds, p = 0.015). However, there were no significant differences between the WU (276.01 ± 13.52 seconds, p > 0.05) and other interventions. Spleen volume compared with baseline was significantly reduced after the apneas by a maximum of ∼45% in the WUAP and by ∼20% in WU. This study showed that the combination of a warm-up with apneas could significantly improve 400-m freestyle swim performance compared with a control and apnea intervention. Further investigation into whether long-term apnea training can enhance this response is justified.